The Influence of Dynamic Capability Competence and Innovation Performance on the Sustainable Competitive Advantage of MSMEs in Papua - Rosiyati M.H Thamrin; Rini Rahmawati; Asrid Juniar; Muhamad Rusmin Nuryadin (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study is novel in its holistic approach to the influence of dynamic capability competency and innovation performance on the sustainable competitive advantage of MSMEs in Papua. This focus fills the gap in the literature that tends to ignore the local context of Papua, especially regarding the adaptation of MSMEs to limitations in infrastructure, technology, and market access. By prioritizing the dimensions of economic, social, and environmental sustainability, this study not only provides academic contributions but also practical recommendations for the long-term development of MSMEs. This study uses a quantitative approach with a survey design. A total of 200 MSME actors were selected through purposive sampling, with the criteria of having implemented technology in their marketing strategies. Primary data were collected through questionnaires, while secondary data came from annual reports and government publications. The main variables—dynamic capability competency, innovation performance, and sustainable competitive advantage—were measured using a Likert scale. The analysis was conducted using path analysis with SPSS and AMOS. The results show that marketing and R&D competencies have a positive influence on innovation performance, which in turn increases sustainable competitive advantage. Innovation performance acts as a mediator in this relationship. The relationship found is unidirectional, emphasizing that competency drives performance, not the other way around. The practical implications of these findings indicate the importance of MSME investment in strengthening internal competencies, especially in marketing and R&D, to create sustainable innovation and strengthen competitive positions amidst Papua's unique limitations.